High complication rate after extendible endoprosthetic replacement of the proximal tibia: a retrospective study of 42 consecutive children. (2nd November 2018) - Tsagozis, Panagiotis; Parry, Michael; Grimer, Robert
Abstract : Background and purpose — The long-term outcome of reconstruction with extendible prostheses after resection of tumors the proximal tibia in children is unknown. We investigated the functional outcome, complication rate and final limb salvage rate after this procedure. Patients and methods — 42 children who had a primary extendible replacement of the proximal tibia for bone tumor with a Stanmore implant between 1992 and 2013 were identified in the department's database. All notes were reviewed to identify the oncological and functional outcomes, the incidence of complications and the rate of amputation. 20 children were alive at final follow-up. Median follow-up time was 6 years and minimum follow-up for surviving patients was 3 years. Results — The overall limb salvage rate was 35/42; amputation was needed in 7 children. 15 implants were revised with a new implant. The Musculoskeletal Tumor Society Score was 73% (40–93) at final follow-up. The overall complication rate was 32/42. Soft tissue problems were the most common mode of complication, noted in 15 children, whereas structural failure and infection occurred in 12 children each. Use of prostheses with non-invasive lengthening was associated with a higher infection rate as compared with conventional ones (4/6 vs. 8/36) and inferior limb survival. Interpretation — Extendible replacements of the proximal tibia allow for limb salvage and satisfactory late functional outcome but have a high rate of complications. The use of non-invasive lengthening implants has not shown any benefit compared with conventional designs and is, rather, associated with higher risk for infection and amputation.